Trans-uretero-cystic external urethral stent for urinary diversion in pediatric laparoscopic pyeloplasty: A novel approach. Issue 42 (16th October 2020) - Dong, Jun-Jun; Wen, Sheng; Liu, Xing; Lin, Tao; Liu, Feng; Wei, Guang-Hui
Abstract: Purpose: We present a new approach for urine drainage in pediatric patients following laparoscopic pyeloplasty, the trans-uretero-cystic external urethral stent (TEUS). Methods: We retrospectively identified 85 children who underwent laparoscopic pyeloplasty from July 2015 to June 2017. The included children were assigned to group A (double-J stent) or group B (TEUS). In group A, the double-J stent was removed by a cystoscopy under anesthesia after 1 month, while in group B, the external stent was removed after 5 to 7 days. We examined the durations of operation, hospital stay and the frequency of stent-related complications including urinary leakage, stent dislocation, stent occlusion, and urinary tract infection. Results: The operation time was significantly longer for patients in group B than for those in group A. No significant difference was observed between the groups regarding stent-related complications. In group A, 4 patients need auxiliary stent re-insertion for the management of complications, 2 developed urinary tract infection, and 2 had stent occlusion. In group B, none needed auxiliary stent re-insertion for complications and avoided re-operation. Conclusions: In children, the outcome of external stent implantation was similar to that using double-J stent, and the use of the former approach may be beneficial for younger children.